A Hybrid Demon Algorithm for the Two-Dimensional Orthogonal Strip Packing Problem. (15th February 2015) - Chen, Bili; Wang, Yong; Yang, Shuangyuan
Abstract : This paper develops a hybrid demon algorithm for a two-dimensional orthogonal strip packing problem. This algorithm combines a placement procedure based on an improved heuristic, local search, and demon algorithm involved in setting one parameter. The hybrid algorithm is tested on a wide set of benchmark instances taken from the literature and compared with other well-known algorithms. The computation results validate the quality of the solutions and the effectiveness of the proposed algorithm.